Dietary patterns, cardiometabolic risk factors, and the incidence of cardiovascular disease in severe obesity. (10th April 2015) - Johns, David J.; Lindroos, Anna‐Karin; Jebb, Susan A.; Sjöström, Lars; Carlsson, Lena M. S.; Ambrosini, Gina L.
<x xml:space="preserve">Abstract</x> Objective The longitudinal associations between a dietary pattern (DP) and cardiometabolic risk factors and cardiovascular disease (CVD) incidence were investigated in a cohort of adults with severe obesity. Methods The analysis included 2, 037 individuals with severe obesity (>34 and >38 kg/m2 for men and women, respectively) from the Swedish Obese Subjects study repeatedly followed up for 10 years. Reduced rank regression was used to identify a DP characterized by dietary energy density, saturated fat intake, and fiber density. Mixed models examined relationships between repeated measures of DP z‐scores and cardiometabolic risk factors. Cox proportional hazards models assessed relationships between DP scores and CVD incidence. Results An energy‐dense, high‐saturated‐fat, and low‐fiber DP was derived. A one‐unit increase in the DP z‐score between follow‐ups was associated with an increase in weight [β (SE)] (1.71 ± 0.10 kg), waist circumference (1.49 ± 0.07 cm), BMI (0.60 ± 0.34 kg/m2), serum cholesterol (0.06 ± 0.01 mmol/l), and serum insulin (1.22 ± 0.17 mmol/l; all P < 0.0001), as well as in serum triglycerides (0.05 ± 0.02 mmol/l; P < 0.05), systolic blood pressure (1.05 ± 0.27 mmHg; P < 0.001), and diastolic blood pressure (0.55 ± 0.16 mmHg; P < 0.05). No significant association was observed between repeated measures of the DP z‐scores and CVD incidence (HR = 0.96; 95% CI = 0.83‐1.12). Conclusions An energy‐dense, high‐saturated‐fat, and low‐fiber DP was longitudinally associated with increases in cardiometabolic risk factors in severe obesity but not with CVD incidence.